Counseling of Anti-Corruption Village Indicators in the Context of Creating Corruption-Free Village Governance: Penyuluhan Indikator Desa Antikorupsi Dalam Rangka Menciptakan Tata Kelola Pemerintahan Desa Bebas Korupsi - Taufik, Iqbal; Nussy, Jennifer Ingelyne; Muammar, Muammar (Faculty of Law, Universitas Pattimura, 2026)
Introduction: The rapid increase in the village budget since 2015 until now, which has reached tens of trillions of rupiah per year, has actually opened a big gap for corrupt practices carried out by village government officials. Various studies and reports show an increasing trend of corruption cases at the village level, with significant state losses and the dominant actors are village heads and village officials. This phenomenon indicates the urgent need for effective preventive efforts to create clean and corruption-free village governance. Purposes of The Devotion: This community service activity aims to increase the knowledge and understanding of actors who are directly involved in the wheel of village government, such as village heads, village government officials, stakeholders, and village communities, regarding the anti-corruption village indicators initiated by the Corruption Eradication Commission. Method of The Devotion: This service activity was carried out in the form of socialization and interactive counseling involving village officials, community leaders, community groups, community organizations, and local governments. The methods used include the delivery of material through presentations (power points) regarding the definition of corruption, forms of corruption in the management of village funds, legal consequences, prevention mechanisms, and the importance of anti-corruption village indicators. This activity began with a pre-test to measure participants' initial understanding, followed by the delivery of material, an interactive panel discussion session for questions and answers and sharing experiences, and ended with a post-test to evaluate the improvement of participants' understanding. Results Main Findings of the Devotion: The results of the activity showed that the majority of participants, especially from the community, initially had a minimal understanding of the serious impact and legal consequences of village fund corruption. After participating in counseling and discussion, there was a significant increase in understanding the definition of corruption, modus operandi that commonly occurs in village fund management, and the importance of anti-corruption village indicators as a prevention instrument. The post-test confirmed that the participants had understood the substance of the material, including the importance of the active role of the community in supervision. This activity succeeded in raising awareness of the urgency of clean and anti-corruption village governance.